EFFECTS OF PETROFILIC MICROORGANISMS AND BULKING AGENT ON HYDROCARBON’S BIODEGRADATION EFFICIENCY - Zulkifliani Zulkifliani; Pujawati Suryatmana; Annisa Rosalina Sylvia; Syafrizal Syafrizal (Scientific Contributions Oil and Gas, 2016)
Bioremediation is a method which can be used to reduce the amount of pollutants or toxic substances that damage the environment through the use of microorganisms to remove the contaminants. The purpose of this research is to determine the effects of petrofilic microorganisms and bulking agent on the enhancement of hydrocarbon’s biodegradation efficiency, soil water content, growth rate of petrofilic bacteria and Azotobacter vinelandii. Nine treatments in this research were a petrofilic consortium (Pseudomonas spp., Actinomycetes sp., and petrofilic fungi) and Azotobacter vinelandii (biosurfactan), as well as bulking agent (rice husk charcoal and baglog waste of Oyster Mushrooms). The experiment design used was a randomized block design with three replications, so there were 27 experimental units (microscosmos). The result was that the application of petrofilic microorganisms and bulking agent is the best treatment to enhance the efficiency of hydrocarbon’s biodegradation, the growth rate of petrofilic bacteria, and soil water content. The petrofilic consortium treatment with the highest value of biodegradation efficiency reached 83,9%.